Assessment Of Antitumor Activity Of Standardized Polyalthia Longifolia Leaf Extract In Hela Cell Tumor Xenograft Mouse Model - Braganza, Cilwyn Shalitha (2022)
P. longifolia is a traditional medicinal plant with a rich source of biologically active phytochemicals. Investigations on methanolic leaf extract were reported to exert potent in vitro anticancer effects on HeLa human cervical cancer cells. Current treatment strategies for cervical cancer are facing challenges such as increased drug toxicity, chemoresistance, and limited treatment options, thus making it imperative for the discovery of safe and effective green anticancer agents. Though P. longifolia is a promising anticancer plant, the in vitro findings by themselves are insufficient to translate to human use and therefore require in vivo preclinical testing. Currently, there are no reports on further investigation of P. longifolia leaf extracts on in vivo animal tumor models, which limits the clinical utility of this plant. Hence this study was conducted to evaluate the in vivo antitumor effects of P. longifolia methanolic leaf extract on HeLa cells xenografted tumors developed in athymic nude mice.